Effect of Testosterone Enanthate Injection and Castration on some Productive Traits of Karadi Lambs - Ishak, M A.; Omar, C A. (Sulaimani Journal for Pure and Applied Sciences, 2014)
This study was conducted to investigate the influence of testosterone enanthate injection on some productive characteristics of Karadi lambs. This experiment was carried out at the Sheep Farm, belong to the Faculty of Agricultural Sciences, University of Sulaimani, Bakrajo. Thirty six Karadi ram lambs, aged 3-4 months and average live weight of 28.7±3.8 kg were randomly divided into three equal groups. Six ram lambs from each group were castrated using elastrator and rubber ring, two weeks before beginning of the experiment. First group was left as control group without treatment (T1). The second group (T2) was injected weekly with 200 mg of testosterone enanthate (TE)/ram lamb. The third group (T3) was injected with 400 mg TE/ram lamb weekly until the termination of the experiment. The TE injections as anabolic agent were given weekly to each treated lamb to investigate its effect on some productive and physiological traits as well as their residual effect, over the period from 18th May to 30th August 2010. Lambs were fed as (3%) of live body weight. The allowance was readjusted at weekly intervals according to live weight. Live body weight (LBW)(Kg), live weight gain(LWG)(%), average daily gain (ADG) (gm/day), dry matter intake (DMI)(gm/day) and feed conversion ratio (FCR)(gm DMI/gm gain) were determined. Results indicated that ADG of intact lambs in the control group, low and high level of TE groups, were higher than the castrated lambs at 4 months of age. The castrated lambs in T2 had higher ADG at 4, 5, 6, 7 and 8 months of age as compared with castrated lambs in T1 and T3 groups. Higher DMI was recorded for the intact lambs of the control, low and high level of TE in comparison with castrated lambs. Results revealed that castrated lambs of the control group had higher FCR at 4,5,6 and 8 months of age as compared to intact lambs (4.06 vs. 3.46, 6.56 vs. 6.41 , 6.96 vs. 5.85 and 5.96 vs. 5.27 gm DMI /gm gain), while the FCR increased in the intact lambs treated with 200 mg TE as compared to castrated lambs at 4,5,6 and 8 months of age (4.00 vs. 3.69, 4.94 vs. 3.93, 5.62 vs. 4.14 and 6.47 vs. 5.44 gm DMI/gm gain), respectively. We concluded that castrated lambs treated with 200 mg TE have higher ADG as compared with other experimental groups.
Keywords: Karadi ram castrated lambs intact lambs TE ADG DMI